The rhetoric and reality of alternative work arrangements (AWA) in Malaysia - Nurhamiza Mumin; Ruth S. Siganul; Ooi, Ai-Yee (IRACST, 2014)
In work-life balance debate, scholars and practitioners underpinned work-related stress as the main problem in their field of concern. However, the introduction of Alternative Work Arrangements (AWA) in the 1970s has shed a light on the difficulty of successfully juggling work and family realms. It allows employees to engross on multiple roles in today’s demanding work environment. This article reviews a range of work-family literature to identify the gap between rhetoric and reality of AWA execution. It emphasizes on flexihour and telecommuting implementation, which are still at a preliminary stage in Malaysia. Through this article, opinion and suggestions will be discussed to enhance the effectiveness of alternative work arrangements in Malaysia. This article suggests more thorough research is needed to determine the applicability of alternative work arrangements in improving public and private sector efficiency.